Inter-annual variation in the trophic niche of Magellanic penguins Spheniscus magellanicus during the pre-molt period in the Beagle Channel - Dodino, Samanta Graciela; Riccialdelli, Luciana; Polito, M.J.; Pütz, K.; Raya Rey, Andrea Nélida (Marine Ecology Progress Series)
Inter-annual variations in the diets of seabirds are often a reflection of resource availability, with population dynamics and community structure implications. We investigated the trophic niche of Magellanic penguins Spheniscus magellanicus during the pre-molt stage in 6 years (2009 and 2013−2017) at Martillo Island, Beagle Channel, Argentina, using carbon and nitrogen stable isotope analysis of feathers. We found higher values in 2009 compared to the other years for both isotopes and estimated different proportions of prey in the diet of Magellanic penguins throughout the years. In 2009, penguins consumed mainly a mixture of benthic and benthopelagic fish, whereas from 2013 to 2017, the proportion of the pelagic form of squat lobster Munida gregaria, considered a key species in the Beagle Channel, increased over time and nearly dominated diets in 2017. Our results confirm that Magellanic penguins act as sentinels, reflecting shifts in the marine community of the Beagle Channel via inter-annual variation in their trophic niche and diet composition. Fil: Dodino, Samanta Graciela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Riccialdelli, Luciana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Polito, M.J. State University of Louisiana; Estados Unidos Fil: Pütz, K. Antartic Research Trust; Alemania Fil: Raya Rey, Andrea Nélida. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego; Argentina